An Essay on Objectives of Business - Mohd Ossama (International Journal of Engineering and Management Research, 2020)
Businesses are tools to provide goods and services to the people; in process they enrich lives and livelihoods. They make our economy strong and stable and fulfil local and national goals as well. This is an essay on the wide ranging objectives of businesses and how they help us to achieve community and societal goals.